60.9k views
0 votes
Solve the following equation for x

Solve the following equation for x-example-1
User LunaVulpo
by
6.2k points

2 Answers

4 votes

Answer:

C

Explanation:

Using the laws of logarithms

• log x + log y ⇔ log(xy)

• log x = log y ⇒ x = y

Given

logx + log(x - 3) = log 3x

log x(x - 3) = log 3x, hence

x(x - 3) = 3x

x² - 3x = 3x ( subtract 3x from both sides )

x² - 6x = 0 ← factor out x from each term

x(x - 6) = 0

Equate each factor to zero and solve for x

x = 0

x - 6 = 0 ⇒ x = 6

Solutions are x = 0, x = 6 → C

User Harrys Kavan
by
5.5k points
7 votes

Answer: OPTION A

Explanation:

You need to remember the logarithms properties:


log(a)+log(b)=log(ab)\\\\log(a)-log(b)=log((a)/(b))\\\\log(a)^b=b*log(a)

Rewrite the equation:


log(x(x-3))=log(3)+log(x)

Like this logarithm has base 10, you can make this procedure:


log(x(x-3))-log(x)=log(3)


log((x(x-3)))/((x))=log(3)


log(x-3)=log(3)


10^(log((x-3)))=10^(log(3))

Then:


(x-3)=3

Now you need to solve for the variable "x":


x=3+3\\x=6

User Mkkekkonen
by
5.9k points